Activation of the gluteus maximus during performance of the back squat, split squat, and barbell hip thrust and the relationship with maximal sprinting - Williams, M. J.; Gibson, N. V.; Sorbie, G.; Ugbolue, U.; Brouner, J.; Easton, C. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this research was to compare muscle activation of the gluteus maximus and ground reaction force between the barbell hip thrust, back squat, and split squat and to determine the relationship between these outcomes and vertical and horizontal forces during maximal sprinting. Twelve, male, team sport athletes (age, 25.0 ± 4.0 years; stature, 184.1 ± 6.0 cm; body mass, 82.2 ± 7.9 kg) performed separate movements of the 3 strength exercises at a load equivalent to their individual 3 repetition maximum. The ground reaction force was measured using force plates and the electromyography (EMG) activity of the upper and lower gluteus maximus and was recorded in each leg and expressed as percentage of the maximum voluntary isometric contraction (MVIC). Subjects then completed a single sprint on a nonmotorized treadmill for the assessment of maximal velocity and horizontal and vertical forces. Although ground reaction force was lower, peak EMG activity in the gluteus maximus was higher in the hip thrust than in the back squat (p = 0.024; 95% confidence interval [CI] = 4-56% MVIC) and split squat (p = 0.016; 95% CI = 6-58% MVIC). Peak sprint velocity correlated with both anterior-posterior horizontal force (r = 0.72) and peak ground reaction force during the barbell hip thrust (r = 0.69) but no other variables. The increased activation of gluteus maximus during the barbell hip thrust and the relationship with maximal running speed suggests that this movement may be optimal for training this muscle group in comparison to the back squat and split squat.